1985
DOI: 10.1002/1097-0142(19850515)55:10<2384::aid-cncr2820551014>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Serum β2 microglobulin in malignant lymphoproliferative disorders

Abstract: Serum beta‐2‐microglobulin (S‐β2M) was measured at diagnosis in 44 patients with lymphocytic leukemias and 47 with malignant lymphomas. Among patients with chronic lymphocytic leukemia (CLL) S‐β2M was raised (>3 mg/1) in 74% and in 23.5% of those with acute lymphoblastic leukemia (ALL). The frequencies for non‐Hodgkin's lymphoma (NHL) and Hodgkin's disease (HD) were 59.2% and 40%, respectively. In CLL patients high serum values correlated with large tumor mass, as estimated by Rai's clinical criteria (P < 0.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
0
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 13 publications
3
6
0
1
Order By: Relevance
“…The discriminating power of the presented stratification could be further improved by incorporating other independent variables for disease progression. In accordance with previous literature (Constantinides et al, 1985;Di Giovanni et al, 1989;Aguilar-Santelises et al, 1992;Hallek et al, 1996), data presented in this study show that the factors predicting disease progression in early untreated B-CLL is underway.…”
Section: Discussionsupporting
confidence: 92%
“…The discriminating power of the presented stratification could be further improved by incorporating other independent variables for disease progression. In accordance with previous literature (Constantinides et al, 1985;Di Giovanni et al, 1989;Aguilar-Santelises et al, 1992;Hallek et al, 1996), data presented in this study show that the factors predicting disease progression in early untreated B-CLL is underway.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, it is assumed that Sb2M values could indicate not only the size but also the proliferative activity of the myeloma cells 13 and could be accepted as a nonspecific maker of tumor mass. 5,6,13,14 In addition, the prognostic role of Sb2M in other proliferative disorders has been confirmed by many authors, 7,14,15 facilitating clinical assessment. 15 On the other hand, it has been reported that in patients with low glomerular filtration rate, Sb2M levels were raised and laboratory findings should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 79%
“…Researchers worldwide have reported the usefulness of Sb2M as a reliable maker in evaluating progression of HIVinfection and multiple myeloma. [5][6][7][8]10,13 In HIV-infected subjects, Sb2M appears to be a better predictor of HIV infection status than CD4 counts and also a better predictor of survival, with increased Sb2M levels being associated with disease progression. 10 Increased production and consequent release of Sb2M into body fluids have been reported in patients with multiple myeloma.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated level of soluble b2m in the serum and urine of patients with autoimmune and malignant diseases has been frequently reported. 30,31 In addition, there are few reports suggesting that b2m can promote proliferation of prostate cancer cells. 32 We wanted to test whether in our experiments the newly expressed b2m protein sheds off the cell surface and potentially can increase tumor cell proliferation.…”
Section: Functional Activity Of Re-expressed Hla Class I Complexmentioning
confidence: 99%